A Nationwide Survey in Japan of Palliative Radiotherapy for Bleeding in Gastrointestinal and Genitourinary Tumor Patients - Kosugi, Takashi (World J Oncol, 2016)
BACKGROUND: In end-stage cancer, bleeding may markedly influence the patient’s quality of life, and radiotherapy plays an important role in the control of the bleeding. In particular, there is no clear evidence of the benefit of palliative radiotherapy for cancers including gastric, rectal, and bladder cancers. A clarification of the current status of palliative radiotherapy for bleeding is needed. METHODS: A survey was conducted by the palliative radiotherapy working group of the Japanese Radiation Oncology Study Group (JROSG), focusing on annual cases of radiotherapy for tumors of the upper and lower gastrointestinal tracts and genitourinary organs (excluding the uterus) and applicable fractionated doses for three hypothetical patients. RESULTS: A total of 54 radiation oncologists at 43 facilities answered. Most of the facilities reported that they conducted hemostatic irradiation for less than one patient per year, though the median annual number of patients treated with radiotherapy in these facilities was 594. The most frequently observed doses per fraction for two of the hypothetical cases were 3.0 and 2.0 Gy. On the other hand, in each case, the numbers of fractions reported varied markedly among the respondents, ranging from 20 Gy in five fractions to over 30 fractions. CONCLUSIONS: Especially in gastric cancer, hemostatic irradiation is rarely performed in most facilities in Japan. An optimal dose fractionation has not been established. Thirty Gy in 10 fractions is one of the most frequently used regimens, but re-bleeding was observed in approximately one-third of the patients.